Digital Parenting: Pola Asuh Orang Tua Mendidik Anak Usia Dini di Era Digital - Setyawati, Novi Suma; Nurdian, Novi; Ilise, Rizki Nugerahani (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to explore parents' parenting patterns in educating early childhood in the digital era. This research approach is qualitative with a narrative study type. The number of informants in this study was 16 people. Data collection techniques using observation, interviews and documentation. The validity of the data used is triangulation. Milles and Hubberman model data analysis technique with steps from data collection, data reduction, data presentation and drawing conclusions. The research results revealed five main themes: (1) variations in parenting patterns, (2) parenting strategies in the digital era, (3) challenges faced by parents, (4) factors that influence parenting patterns, and (5) the role of PAUD institutions and Society. These findings provide insight into the complexities of parenting in the digital era and highlight the importance of support and education for parents